Cognitive impairment among older persons with chronic illness attending primary care and its association with cardiovascular risk using the Framingham risk score - Nimelesh Balanthiren; Mohd Fairuz Ali; Aznida Firzah Abdul Aziz (BMC Geriatrics)
Abstract Background Dementia is a major public health burden, particularly among the older persons with significant implications for individuals, caregivers, and society. Identifying mild cognitive impairment early can facilitate timely intervention and care.This cross-sectional study aims to investigate the association between Framingham risk score (FRS), a widely used tool for cardiovascular disease (CVD) risk prediction, and cognitive impairment among older persons with chronic illness in Malaysia. Methods A total of 289 participants aged 60 years and above with chronic illness were recruited from Klinik Primer Hospital Tuanku Chanselor Muhriz via simple random sampling via computer generator. The Montreal Cognitive Assessment Bahasa Malaysia version (MoCA-BM) was used to assess cognitive function and the FRS was calculated on the basis of CVD risk factors. Results The prevalence of cognitive impairment among the participants was found to be 19.7%. Multiple Logistic Regression revealed that age (AOR 1.101, 95% CI = 1.041,1.163, p < 0.001), systolic blood pressure (AOR 1.048, 95%CI = 1.024, 1.072, p < 0.001) diabetes (AOR 2.655, 95% CI = 1.194, 5.906, p = 0.017) increased the odds of having cognitive impairment among older persons with chronic illness whereas secondary education ( AOR 0.087, 95% CI = 0.008, 0.963, p = 0.047) and higher education ( AOR 0.037, 95% CI = 0.002, 0.833, p = 0.038) reduced the likelihood of having cognitive impairment. Individuals with higher FRS were more likely to have cognitive impairment (AOR 1.099, 95% CI = 1.049, 1.172, p < 0.001). The optimal cutoff point for the FRS to determine cognitive impairment is 30 for males with a sensitivity and specificity of 84.4% and 51.2% while the optimal cut off point for females is 18.5 with a sensitivity and specificity of 76% and 63.1% respectively. Conclusions These findings suggest that the FRS which was originally designed for CVD risk assessment may also serve as a valuable predictive tool for cognitive impairment among older persons with chronic illness. Integrating FRS into routine primary care assessments could enhance the early identification of individuals at risk and enable appropriate cognitive screenings and interventions. Further research such as a longitudinal cohort study in a larger and more diverse population is warranted to validate the association of CVD risks with the development of dementia.